Vasectomy and prostate cancer risk in the European Prospective Investigation Into Cancer and Nutrition (EPIC) - Smith Byrne, K; Castaño, J; Chirlaque, M; Lilja, H; Agudo, A; Ardanaz, E; Rodríguez-Barranco, M; Boeing, H; Kaaks, R; Khaw, K; Larrañaga, N; Navarro, C; et al. (American Society of Clinical Oncology, 2017)
Purpose Vasectomy is a commonly used form of male sterilization, and some studies have suggested that it may be associated with an increased risk of prostate cancer, including more aggressive forms of the disease. We investigated the prospective association of vasectomy with prostate cancer in a large European cohort, with a focus on high-grade and advanced-stage tumors, and death due to prostate cancer. Patients and Methods A total of 84,753 men from the European Prospective Investigation into Cancer and Nutrition (EPIC), aged 35 to 79 years, provided information on vasectomy status (15% with vasectomy) at recruitment and were followed for incidence of prostate cancer and death. We estimated the association of vasectomy with prostate cancer risk overall, by tumor subtype, and for death due to prostate cancer, using multivariable-adjusted Cox proportional hazards models. Results During an average follow-up of 15.4 years, 4,377 men were diagnosed with prostate cancer, including 641 who had undergone a vasectomy. Vasectomy was not associated with prostate cancer risk (hazard ratio [HR], 1.05; 95% CI, 0.96 to 1.15), and no evidence for heterogeneity in the association was observed by stage of disease or years since vasectomy. There was some evidence of heterogeneity by tumor grade ( P = .02), with an increased risk for low-intermediate grade (HR, 1.14; 95% CI, 1.01 to 1.29) but not high-grade prostate cancer (HR, 0.83; 95% CI, 0.64 to 1.07). Vasectomy was not associated with death due to prostate cancer (HR, 0.88; 95% CI, 0.68 to 1.12). Conclusion These findings from a large European prospective study show no elevated risk for overall, high-grade or advanced-stage prostate cancer, or death due to prostate cancer in men who have undergone a vasectomy compared with men who have not.